The effect of human papillomavirus status on prognosis and local treatment strategies of T1-2N0 oropharyngeal squamous cell cancer - Zhou, Ping; Chen, Deng-Lin; Lian, Chen-Lu; Wu, San-Gang; Zhang, Shi-Yang (Frontiers in Public Health, 2022)
Purpose To explore the effect of human papillomavirus (HPV) status on prognosis and further investigate whether human papillomavirus (HPV) status has an impact on the local treatment strategies for T1-2N0 oropharyngeal squamous cell cancer (OPSCC) patients. Methods Patients diagnosed with T1-2N0 OPSCC between 2010 and 2015 were included from the Surveillance, Epidemiology, and End Results database. Data were analyzed using propensity score matching (PSM), Chi-square test, Kaplan-Meier survival analysis, and Cox multivariable analyses. Results A total of 1,004 patients were identified, of whom 595 (59.3%) had HPV-related tumors. Of all the patients, 386 (38.4%) and 618 (61.6%) received definitive radiotherapy and radical surgery, respectively. HPV status had no significant effect on local treatment strategies for early-stage OPSCC (P = 0.817). The 3-year cancer-specific survival (CSS) and overall survival (OS) were 89.6 and 80.1%, respectively. Compared to those with HPV-negative diseases, patients with HPV-positive diseases had better CSS and OS. A total of 222 pairs of patients were completely matched after PSM. The results of multivariate Cox regression analysis showed that patients with HPV-positive disease had significantly better CSS (P = 0.001) and OS (P < 0.001) compared to those with HPV-negative tumors. However, local treatment strategy was not associated with survival outcomes after PSM (CSS, P = 0.771; OS, P = 0.440). The subgroup analysis showed comparable CSS and OS between those treated with radical surgery and definitive radiotherapy regardless of HPV status. Conclusions HPV status is an independent prognostic factor for the survival of stage T1-2N0 OPSCC patients. Local treatment strategies had no significant effect on the survival of early-stage OPSCC regardless of HPV status. Patients with early-stage OPSCC should be informed regarding the pros and cons of definitive radiotherapy or radical surgery.